(untitled) - Stallings, William (Indianapolis, 1990)
This book is one of a series of books that provides a comprehensive treatment of computer-comunications standards, presented within the framework of the OSI model.
Keywords: Hệ thống truyền dữ liệu,Data transmission systems; Tiêu chuẩn,Standards